Analysis of the Seeming Conflicts in the Division of Powers Between Directors and Members of the Company in General Meeting - Obinuchi, Chimezule (ABUAD Law Journal, 2023)
A company is a legal personality distinct and separate from its owner. It can sue and be sued in its name. The extant law, Companies and Allied Matters Act described it as having all the powers of a natural person of full capacity. This paper critically examines the conflicts which are bound to arise in company operation and administration. The directors of companies on one hand see themselves as the engine room and life wire of the company, on the other hand the members who are shareholders see themselves as the ‘owners’ andwatchdog of the company. It is obvious from the above scenario that conflicts are bound to arise between the directors and members in general meeting of the company. This research work explains in details the law of meeting and types bringing out the new innovations introduced in the new Act as it relates to what constitutesordinary business of Annual General Meeting of company. It is the finding of this research that serious conflict exist between the directors of companies and members especially where the directors exercises powers that are ultravires their powers but intravires the powers of the company.This research concludes that where such exercise ofpowers by directors are for the benefit of the company it should be ratified by members in general meeting for the good of the company. Cooperation between the members and directors for the growth of the company should be the utmost desire of all.